DESIGN AND CONSTRUCTION OF SOIL MOISTURE DETECTION TOOL USING ANDROID BASED DECISION TREE ALGORITHM - Aziz Ritonga, Mirwan; Tanti, Lili (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: Soil moisture is an important factor in determining the watering needs of plants for optimal growth. Therefore, accurate monitoring of soil moisture is necessary. This research aims to design and build a soil moisture detection tool based on the Decision Tree algorithm with the support of the YL-69 sensor for humidity measurement and the DHT11 sensor for temperature measurement to increase data accuracy. This system uses NodeMCU ESP8266 as a microcontroller and is integrated with an Android application as a user interface. Sensor interpretation data is analyzed using the Decision Tree algorithm to determine soil conditions (dry, damp or wet). The test results show an accuracy level of 95% from 300 data samples. Thus, this system is able to detect soil moisture effectively and can help increase the efficiency of crop management on a household and commercial agricultural scale. Keywords: agriculture, android, decision tree algorithm, sensors, soil moisture detection